D4N2024 Presentation Showcase – Thematic Session 3a: Why we eat what we eat: drivers of food choice - Ahsan, Ali; Patwardhan, Sharvari; Sitisekara, Hasara; Bharadwaz, Mrinmoy P.; Nasim, Zarmeen; Rahman, Lamisa; Akter, Mahsina Syeda; Rahman, Tareq; Kabir, A.N.M. Faijul; Lenora, Pahanma; Goonawardhana, Malitha; Lumanthi, Sedhara; et al. (International Food Policy Research Institute, 2024)
D4N2024 Presentation Showcase – Thematic Session 3a: Why we eat what we eat: drivers of food choice